The significance of data collection, data analysis and data incorporation in E-Business and distribution through Management Information System (MIS) of ShopUp - Nanjiba, Rifa (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.